APOEε4 Genotype Is Related to Brain Amyloid Among Mexican Americans in the HABS-HD Study - O'Bryant, Sid E.; Petersen, Melissa; Hall, James; Johnson, Leigh (Frontiers in Neurology, 2022)
Introduction Despite the fact that Hispanics are expected to experience the greatest increase in Alzheimer's disease (AD) and related dementias (ADRDs) by 2060, very little data is available regarding the fundamental biomarkers of AD among Mexican Americans who reflect the majority of Hispanics in the U.S. Here we sought to examine the link between APOEε4 genotype and brain amyloid among Mexican Americans as compared to non-Hispanic white participants from the Health & Aging Brain Study – Health Disparities (HABS-HD) cohort. Methods PET amyloid (florbetaben) data were analyzed from 105 Mexican American and 150 non-Hispanic white participants. Results Among Mexican Americans, APOEε4 genotype presence was associated with Global SUVR (p = 0.003) as well as amyloid burden in the frontal (p < 0.001), lateral parietal (p = 0.003), lateral temporal (p = 0.008) and anterior-posterior cingulate (p = 0.005) regions of interest (ROIs). Among non-Hispanic white participants, APOEε4 genotype presence was associated with Global SUVR (p < 0.001) as well as amyloid burden in the frontal (p < 0.001), lateral parietal (p < 0.001), lateral temporal (p < 0.001) and anterior-posterior cingulate (p < 0.001) regions of interest (ROIs). The association between APOEε4 genotype and cerebral amyloid was strongest among non-Hispanic white participants. Discussion/Conclusion Despite the fact that the APOEε4 genotype is significantly less frequent among Mexican Americans, its presence remains to be a significant risk factor among this group for AD pathological burden across all regions. Additional work is needed to understand the presence, progression, and clinical impact of brain amyloid among Mexican Americans.